Globular Glial Tauopathy Type I Presenting as Atypical Progressive Aphasia, With Comorbid Limbic-Predominant Age-Related TDP-43 Encephalopathy - Rusina, Robert; Csefalvay, Zsolt; Kovacs, Gabor G.; Keller, Jiri; Javurkova, Alena; Matej, Radoslav (Frontiers in Aging Neuroscience, 2019)
Globular glial tauopathies (GGT) have heterogeneous presentations with little available information regarding typical clinical manifestations. We report on a case of atypical primary progressive aphasia due to comorbid GGT and limbic TDP-43 proteinopathy. The initial clinical phenotype was compatible with the nonfluent-agrammatical variant of primary progressive aphasia and early hippocampal amnesia. Progressively, parkinsonism and supranuclear oculomotor impairment occurred, and finally, late mutism with frontal type dementia, impaired comprehension, and behavioral manifestations developed. The neuropathology was characteristic of globular glial tauopathy type I with vascular changes and comorbid limbic-predominant age-related TDP-43 encephalopathy (LATE). Our findings expand the clinical spectrum of globular glial tauopathies to include a complex progressive aphasia syndrome. The extraordinary feature, in this case, was the combination of two progressive aphasia subtypes, i.e., the early nonfluent-agrammatical variant and the late semantic variant. Our findings also expand the spectrum of neuropathological comorbidities in GGT.